KARAKTERISTIK FISIKOKIMIA DAN SENSORIS DAGINGANALOG BERBASIS BONGGOL PISANG (Musa paradisiaca) DAN JAMUR GERIGIT (Schizophyllum commune) DENGANVARIASI BAHAN PENGIKAT) - Nuria Zaidatur Rabiah; Lina Widawati; Hesti Nur'aini (Jurnal Agriovet, 2026)
Analog meat is a product made from vegetable protein that has properties similar to animal meat. The use of split gill mushrooms acts as a fibrous texture former resembling meat, banana pseudostem as a source of fiber and natural binders, and soy protein isolate and egg white as a structural strengthener and increase the protein content of the product. This study aims to determine the characterize the physical, chemical, and organoleptic qualities and analyze the benefits of analog meat products. This study used a completely randomized design (CRD) methodology consisting of two factors and three repetitions, the first factor is soy protein isolate and egg white (10% and 10%) the second factor is the composition of split gill mushrooms and banana pseudostem consisting of three levels (75%, 50%, 25%). The results showed that the average value of analog meat yield was between 90.80% to 99.33%. The average value of water content was between 60.59% to 68.83%. The average value of protein content was between 14.81% to 22.06%. The average fiber content ranged from 6.44% to 17.66%. The best treatment in this study was the addition of 50% banana pseudostem, 50% jagged fungus, and egg white binder, with organoleptic test scores of 3.60 (like), 3.35 (somewhat like), 3.60 (like) and 3.60 (like) for taste. The business analysis showed a R/C ratio of 1.30, indicating that the analog meat processing business is feasible and profitable to develop. Keywords: Analog meat, banana pseudostem, soy protein isolate, split gill  mushrooms, egg white